Strategi Efektif Pembinaan Iman Anak Sekolah Minggu melalui Metode Pengajaran Alat Peraga Sekolah Minggu - Cindi Manik; Michael Sianipar; Pulo Aruan (Sekolah Tinggi Teologi Gereja Kalimantan Evangelis, 2026)
In the HKBP church, Sunday school children are one of the valuable assets that will become the next generation of church development, because Sunday school children are an important part of church life and the future of Christian ministry. Based on Mark 10:14, it shows Jesus' great concern for children and affirms that they are worthy of receiving the Kingdom of God. This statement emphasizes the importance of making children part of the main concern in ministry, especially in teaching God's word from an early age. This paper aims to highlight the urgency of developing the faith of Sunday school children through creative and innovative methods that are relevant to today's children, namely by utilizing creative teaching aids taken from natural materials. Through Community Service (PkM) activities at HKBP Hutahaean, it is intended to demonstrate that the role of teaching aids not only increases children's ability to grasp biblical messages, but also further arouses their enthusiasm to know and love God. In this study, a seminar was also conducted for Sunday school teachers in the application of this teaching method by introducing a teaching aid book distributed by the HKBP Theological College institution, so that Sunday school teachers are expected to develop this contextual teaching method to meet the learning needs of Sunday school children in their faith growth.